Evaluación de dos híbridos de Brócoli (Brassica oleracea var. itálica) a tres Métodos Alternativos, aplicados a dos dosis, para el control de Hernia de la col (Plasmodiophora brassicae Wor.)”, en la Hacienda Limache – Mulaló – Cotopaxi - Almachi Paneluisa, Victor Ernesto (2013)
The present research was made in the Cotopaxi Province, Latacunga Canton, Mulaló Parrish, Rumipamba de Espinosas District, Limache Farm, located at 00 ° 46'18 "south latitude and 78 ° 37'38 " west longitude with 10.5 ° C average temperature, 65.5 % relative humidity to 2950 m.a.s.l., with an annual rainfall of 748mm, it was developed the growing phase to open field since transplanting up harvest in a sandy loam soil, with pH 6.9. The main objective was to determine the resistance of hybrids which of alternative methods of control is the most efficient and the better dose. The get results in the research allowed to determine: what the Domador hybrid is the best, so also the product that the better results was introduced AgriSafe, with the dose one, finally, it is closed that the best treatment was h1p3d1 ( AgriSafe tamer + dose + 1) for having 20803 kg/ha yield , with a production cost of $ 3,203.7/ha, so the best benefit cost 1.75. We recommend planting Domador hybrid and use the AgriSafe product, with a dose of 1 lt/ha, as rooted for stimulate roots, as an alternative method of the cabbage hernia control